Generalized criterion for the onset of particle deposition in crossflow microfiltration via DOTM : modeling and experimental validation - Zamani, Farhad (2014)
The concept of a critical permeation flux for the onset of particle deposition in crossflow microfiltration (CFMF) is well-established. However, the critical flux is known to be a function of process parameters such as the particle size, bulk concentration and crossflow velocity. In the present study, the critical modified Peclet number (Pecrit) is explored instead as a generalized criterion for the onset of particle deposition that incorporates the effects of these process parameters as well as the axial position along the membrane. A proper determination of Pecrit requires an accurate prediction of the concentration polarization boundary layer thickness δc and shear-induced diffusion coefficient Ds. The classical Lévêque model is adapted to allow for the effect of the permeation flux on the velocity profile. Moreover, the assumptions of a constant concentration at the membrane surface cw and constant Ds that have been made in prior studies are relaxed in an improved numerical solution to the convective diffusion equation that is used to predict δc and Ds. The critical permeation flux is determined from particle deposition data taken for 6 and 10 μm latex spheres via Direct Observation Through the Membrane (DOTM) characterization. A constant value of Pecrit=4.00±0.08 is found to characterize the effects of particle diameter, bulk concentration and crossflow velocity as well as axial position on the onset of particle deposition.